Effect of coexistent coarctation of pulmonary trunk in natural history of complete absence of pulmonary valve with ventricular septal defect. Issue 9 (September 1975) - Peter, T; Harper, R; Vohra, J; Hunt, D
Abstract : A case of complete absence of the pulmonary valve in association with a ventricular septal defect and a pulmonary artery coarctation is described. Despite these defects the patient had minimal symptoms, probably because the pulmonary artery coarctation acted as a natural banding and limited the pulmonary regurgitant flow and reduced the left-to-right shunt across the ventricular septal defect. The patient was operated on at the age of 40 and the ventricular septal defect was closed but the pulmonary artery coarctation was left alone. In view of the long-term survival in this case, it is suggested that pulmonary artery banding would reduce the symptoms and increase the life expectancy of patients with congenital absence of the pulmonary valve and a ventricular septal defect.